O feminino em a carne, de Júlio Ribeiro. - Sousa, Eva Pereira Barbosa (Universidade Federal do Tocantins, 2022)
This paper analyzes the feminine in the work A carne, by Júlio Ribeiro. It is a naturalist novel published in the late nineteenth century, more precisely in 1888. In this sense, the study is justified by the need to research how the feminine is presented in the course of the novel. By analyzing the work, we intend to verify that Lenita is a woman ahead of her time. Therefore, the proposal is to raise a reflection about the women in the mentioned work from the general aim, which is to analyze the character Lenita, in Júlio Ribeiro's naturalist narrative. The specific aims of the study are: to identify in the novel, A carne, the representation of women; to approach naturalism in a work of great repercussion in Brazilian literature; to observe the characteristics of the feminine in the protagonist Lenita, through essays that discuss the feminine in literature. Thus, the methodology adopted to accomplish the purposes of this paper consisted in a bibliographic survey to support reflections on the role of the female character in the narrative.